Driving Brand Engagement: Exploring Brand Touchpoints and Self-Congruity in Local Furniture Retail - Widyastuti, Pristiana (Forum Kerjasama Pendidikan Tinggi, 2024)
This study investigates the relationships between brand touchpoints, self-congruity, and brand engagement in Indonesia's local furniture market. A quantitative approach focused on customer touchpoints and self-congruity as independent variables, with brand engagement as the dependent variable. The sample comprised 100 respondents who had made multiple purchases from various furniture stores, both online and offline, located in the Greater Jakarta area. Data collection involved questionnaires utilizing a Likert scale to measure relevant indicators. Structural Equation Modeling (SEM) was used for data analysis, specifically confirmatory SEM and SmartPLS as tools to assess causal relationships among the variables. The study's results present significant relationships between customer touchpoints and self-congruity with brand engagement. The path coefficients show that customer touchpoint has a positive and significant impact on brand engagement, with a t-statistic value of 4.694, more than 1.96 (P-value lower than 0.05). Then, self-congruity has a positive and significant impact on brand engagement, with a t-statistic value of 3.737, more than 1.96 (P-value lower than 0.05). Effective customer touchpoints enhanced customer engagement significantly, while self-congruity contributed to a deeper emotional connection between customers and brands. The findings suggest that consumers are likelier to engage with brands that reflect their personal styles and identities, fostering loyalty and commitment. This research highlights the importance of creating meaningful brand interactions and aligning brand messaging with consumer identities to enhance engagement within brand touchpoints.